The Emerging Roles of circFOXO3 in Cancer - Rao, Dean; Yu, Chengpeng; Sheng, Jiaqi; Lv, Enjun; Huang, Wenjie (Frontiers in Cell and Developmental Biology, 2021)
Circular RNAs (circRNAs) are a class of endogenous non-coding RNAs which are mainly formed by reverse splicing of precursor mRNAs. They are relatively stable and resistant to RNase R because of their covalently closed structure without 5' caps or 3' poly-adenylated tails. CircRNAs are widely expressed in eukaryotic cells and show tissue, timing and disease specificity. Recent studies have found that circRNAs play an important role in many diseases. In particular, they affect the proliferation, invasion and prognosis of cancer by regulating gene expression. CircRNA Forkhead box O3 (circFOXO3) is a circRNA confirmed to be abnormally expressed in a variety of cancers, including prostate cancer, hepatocellular carcinoma, glioblastoma, bladder cancer, breast cancer, etc. At present, the feature of circFOXO3 as a molecular sponge is widely studied to promote or inhibit the development of cancers. However, the diverse functions of circFOXO3 have not been fully understood. Hence, it is important to review the roles of circFOXO3 in cancers. This review has summarized and discussed the roles and molecular mechanism of circFOXO3 and its target genes in these cancers, which can help to enrich our understanding to the functions of circRNAs and carry out subsequent researches on circFOXO3.